Snake bite induced delayed hypopituitarism: a rare case report - Bhowmick, Niladri; Mukhopadhyay, Jotideb; Kar, Soumyadip; Das, Amrita (International Journal of Research in Medical Sciences, 2020)
Hypopituitarism following snake bite induced AKI and dialysis is an uncommon complication. Often the presentation is delayed and Can present with a myriad of features. We present a case of a 27 year old male patient, with past history of snake bite and acute kidney injury (AKI) requiring dialysis and which subsequently resolved, presenting to us with fatigability and weakness, absence of secondary sexual character and poor academic performance. On examination, the patient had pale white and coarse skin. Hoarseness of voice was present. There was proximal upper and lower limb muscle weakness present with pseudo myotonia on examination. There was loss of axillary and pubic hair with low testicular volume. Routine reports suggested mildly elevated creatinine with severely elevated Triglyceride levels. Creatine phosphokinase (CPK) was raised. Hormonal profile revealed low free thyroxine (FT4) and serum 8 a.m. Cortisol but an inadequate increase in thyroid stimulating hormone (TSH) and adrenocorticotropic hormone (ACTH) levels were suggestive of central hypopituitarism. Luteinizing hormone (LH), follicle-stimulating hormone (FSH), Insulin-like growth factor 1 (IGF-1) levels were reduced. Neuroimaging revealed empty sella suggestive of pituitary apoplexy. The above were suggestive of delayed hypopituitarism following post snake bite dialysis mediated pituitary apoplexy. In all cases of snake bite, a common occurrence in our country the possibility of hypopituitarism should be kept in mind and the hormonal profile followed up closely along with the renal parameters.